Memimpin Dengan Hati - Natalia Rotua Sianipar; Renisha Wikawanty Lumban Raja; Ibelala Gea (Jurnal Pendidikan Agama dan Teologi, 2023)
Leaders are important because leaders are the key to the success of an organization. At this time, many leaders did not use their hearts in leading. They often use reason so that it sometimes causes problems. Of course this is very unfortunate if the leader cannot carry out his duties properly. The research method used by the author is a qualitative approach by applying library research methods. The purpose of this research is that someone who wants to become a leader can understand how to lead with heart and can have the character of being responsible, committed, and determined.